2015
DOI: 10.1016/j.jaut.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal injury promotes nephritis flare in lupus-prone mice

Abstract: Systemic lupus erythematosus is clinically characterized by episodes of flare and remission. In patients, cutaneous exposure to ultraviolet light has been proposed as a flare trigger. However, induction of flare secondary to cutaneous exposure has been difficult to emulate in many murine lupus models. Here, we describe a system in which epidermal injury is able to trigger the development of a lupus nephritis flare in New Zealand Mixed (NZM) 2328 mice. 20-week old NZM2328 female mice underwent removal of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Other types of skin injury such as tape stripping and topical application of a TLR7 agonist have been reported to enhance kidney injury in certain lupus models, although disease enhancement was thought to be mediated by macrophages and dendritic cells rather than neutrophils 68,69 . Having demonstrated that tape stripping did not lead to neutrophil recruitment to the kidney, we propose that UV light exposure is different from other types of sterile skin inflammation and is more relevant to SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of skin injury such as tape stripping and topical application of a TLR7 agonist have been reported to enhance kidney injury in certain lupus models, although disease enhancement was thought to be mediated by macrophages and dendritic cells rather than neutrophils 68,69 . Having demonstrated that tape stripping did not lead to neutrophil recruitment to the kidney, we propose that UV light exposure is different from other types of sterile skin inflammation and is more relevant to SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which the inflammasome impacts SLE pathogenesis are being defined. Upregulation of inflammasome gene expression and inflammasome activity has been identified in both human and murine lupus (1,2,4,6,7,44). Inhibition of caspase 1-or NLRP3-mediated inflammasome signaling in murine models demonstrated that inflammasome pathways contribute to disease pathogenesis via promotion of autoantibody production, endothelial dysfunction, and nephritis (5,9,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…In lupus-prone mice, CCR1, CCR5, and their ligands are increased in the kidney during LN development [ 24 , 25 , 28 , 49 – 52 , 54 , 75 , 76 ]. Studies have shown that, in nephritic NZB/W F1 mice, both renal T cells and monocytes/macrophages have elevated CCR1 expression on the surface [ 50 ].…”
Section: Key Chemokines and Chemokine Receptors In Lnmentioning
confidence: 99%